Analysis of the methods of determining their hardness indicators during stretching of textile fabrics - Fattayev, Muhammadjon Avazbek o’g’li; Vasiyeva, Muslimaxon Hayrullo qizi (Science and Education, 2023)
In this article, the stretching properties of fabrics during the production of textile fabrics are analyzed based on the standard requirements.